2007
DOI: 10.1002/joc.1460
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different procedures to map reference evapotranspiration using geographical information systems and regression‐based techniques

Abstract: Abstract:This paper compares different procedures for mapping reference evapotranspiration (ET o ) by means of regression-based techniques and geographical information systems (GIS). ET o is calculated following the method of Hargreaves (HG) from a dense database of meteorological stations in the northernmost semi-arid region of Europe, the Ebro valley. The HG method requires the calculation of estimates of extraterrestrial radiation (R a ). We calculated this parameter using two approaches: (1) the common app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 73 publications
(74 reference statements)
0
26
0
2
Order By: Relevance
“…We demonstrated that the local and spatially complex nature of fogs makes them more difficult to map than other climatic variables such as precipitation and temperature for which it is common to obtain high R 2 values for regression models, usually higher than 0.7 (Ninyerola et al, 2007a(Ninyerola et al, , 2007b. R 2 values higher than 0.7 have been obtained previously for the Aragón region in monthly regression models of precipitation and temperature (Vicente-Serrano et al, 2003;Vicente-Serrano et al, 2007;López-Moreno et al, 2007). In contrast, fog-frequency models for this region yield R 2 values between 0.48 and 0.72 for the winter months, and only consider non-linear relationships by means of GAMs.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We demonstrated that the local and spatially complex nature of fogs makes them more difficult to map than other climatic variables such as precipitation and temperature for which it is common to obtain high R 2 values for regression models, usually higher than 0.7 (Ninyerola et al, 2007a(Ninyerola et al, , 2007b. R 2 values higher than 0.7 have been obtained previously for the Aragón region in monthly regression models of precipitation and temperature (Vicente-Serrano et al, 2003;Vicente-Serrano et al, 2007;López-Moreno et al, 2007). In contrast, fog-frequency models for this region yield R 2 values between 0.48 and 0.72 for the winter months, and only consider non-linear relationships by means of GAMs.…”
Section: Discussionmentioning
confidence: 51%
“…Many previous studies have mapped climate parameters such as precipitation (Ninyerola et al, 2000(Ninyerola et al, , 2007aBrown and Comrie, 2002), temperature (Vicente-Serrano et al, 2003;Ninyerola et al, 2007b), evapotranspiration (Martínez-Cob, 1996;Vicente-Serrano et al, 2007), and snow depth (López- Moreno and Nogués-Bravo, 2005). The climate variables that have received the greatest attention are precipitation and temperature, as maps of these variables are of great interest for numerous applications.…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of this approach might not be for flat terrain, in which relief does not significantly affect R a . However, in complex terrain, for high-resolution ET o maps used for ecological and water resources management, spatial variations in relief are commonly very important and significantly affect the values of R a estimates because radiation flux are especially dependent on the geometry of terrain [15], and this has a significant effect on local ET o values [45].…”
Section: Discussionmentioning
confidence: 99%
“…Then, T mean was spatially modelled based on MLR relationships for each month. The main advantage of this technique is that maps are compiled not only from information from various weather stations, but also from auxiliary information that describes geographic and topographic variables; this improves the accuracy and spatial detail of the resulting maps (Vicente-Serrano et al 2007). …”
Section: Spatial Distribution Of Etmentioning
confidence: 99%
“…The results indicated that the FAO-Penman equation was the best model to estimate ET 0 , and the spatially-modelled ET 0 values (R 2 = 0.88) were in agreement with the corresponding in situ data. Vicente-Serrano et al (2007) compared different procedures for mapping the Hargreaves model ET 0 by means of regressionbased techniques and GIS in the northernmost semiarid region of Europe, the Ebro Valley. They calculated the extra-terrestrial radiation (R a ) parameter using two approaches: (a) determination of R a as a function of latitude; and (b) estimation of the parameter using a digital terrain model (DTM) and GIS modelling.…”
Section: Introductionmentioning
confidence: 99%